2016
DOI: 10.4103/2249-4863.197324
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anti-filarial antibody among hydrocele patients living in an endemic area for filariasis

Abstract: Background:The knowledge of the current prevalence of lymphatic filariasis and its transmission will be helpful in its elimination. Thus, the present study is aimed to determine its prevalence among hydrocele patients which is a common presentation in chronically infected cases.Materials and Methods:One hundred patients suffering from hydrocele admitted to the surgical ward were included in the study. Blood samples were collected from the patients during the day hours for the detection of anti-filarial antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
3
5
0
Order By: Relevance
“…The prevalence of microfilaremia was 3.3% in this study. These findings were consistent with the studies of Khandelwal et al, Shah et al, Goel et al and Singh et al 25,[27][28][29] Khandelwal et al retrospective study of clinically unexpected filariasis observed smears revealed microfilaria in 15 out of the 16 cases. Fragments of adult worms in 3 cases; and embryoid bodies in two cases, both these cases were from lymph node swelling.…”
Section: Microfilaria In Peripheral Blood Smearsupporting
confidence: 92%
See 4 more Smart Citations
“…The prevalence of microfilaremia was 3.3% in this study. These findings were consistent with the studies of Khandelwal et al, Shah et al, Goel et al and Singh et al 25,[27][28][29] Khandelwal et al retrospective study of clinically unexpected filariasis observed smears revealed microfilaria in 15 out of the 16 cases. Fragments of adult worms in 3 cases; and embryoid bodies in two cases, both these cases were from lymph node swelling.…”
Section: Microfilaria In Peripheral Blood Smearsupporting
confidence: 92%
“…There was significant association of anti-filarial antibody and peripheral blood smear findings as per Chi-square test (p<0.05). This is in concordance to the studies of Goel et al and Singh et al 25,28 Goel et al study to assess the association between isolated non-communicable hydrocele and filariasis showed that out of 14 cases who were positive for serum anti-filarial antibody, microfilaria was positive in peripheral smear of only one patient. 25 Singh et al prospective, cross-sectional, observational study determining its prevalence among hydrocele patients in chronically infected cases observed microfilaremia detected by peripheral blood smear examination showed that out of 21 anti-filarial antibody positive patients, 5 (23.8%) patients showed microfilaria in their blood.…”
Section: Association Between Ant-filarial Antibody and Microfilaria In supporting
confidence: 90%
See 3 more Smart Citations